Passive transfer of modest titers of potent and broadly neutralizing anti-HIV monoclonal antibodies block SHIV infection in macaques - Shingai, Masashi; Donau, Olivia K.; Plishka, Ronald J.; Buckler-White, Alicia; Mascola, John R.; Nabel, Gary J.; Nason, Martha C.; Montefiori, David; Moldt, Brian; Poignard, Pascal; Diskin, Ron; Bjorkman, Pamela J.; et al. (The Journal of experimental medicine, 2014)
It is widely appreciated that effective human vaccines directed against viral pathogens elicit neutralizing antibodies (NAbs). The passive transfer of anti–HIV-1 NAbs conferring sterilizing immunity to macaques has been used to determine the plasma neutralization titers, which must be present at the time of exposure, to prevent acquisition of SIV/HIV chimeric virus (SHIV) infections. We administered five recently isolated potent and broadly acting anti-HIV neutralizing monoclonal antibodies (mAbs) to rhesus macaques and challenged them intrarectally 24 h later with either of two different R5-tropic SHIVs. By combining the results obtained from 60 challenged animals, we determined that the protective neutralization titer in plasma preventing virus infection in 50% of the exposed monkeys was relatively modest (∼1:100) and potentially achievable by vaccination.